Learn Filipino through English-Filipino, Filipino-English word listings and common expressions - Belvez, Paz M. (Rex Books Store, 2000)
A bilingual (English-Filipino) vocabulary listing consisting of translations, pronunciations, syllabications and common everyday expressions that serves as an aid in learning and speaking Filipino.